PENGELOLAAN LIMBAH MEDIS RUMAH SAKIT DARURAT WISMA ATLET DALAM PENANGANAN COVID-19 BERDASARKAN HUKUM LINGKUNGAN INTERNASIONAL - Aulina Nadhira Mirranti; Anto Ismu Budianto (Faculty of Law, Universitas Trisakti, 2023)
Environmental threats due to medical waste management problems have increased due to the Corona Virus Disease 19 (Covid-19) pandemic. Indonesia has experienced an increase in medical waste due to the Covid-19 pandemic, so that medical waste management at the Wisma Atlet Emergency Hospital needs more attention. The problem in this study, namely whether the medical waste management rules at the Wisma Atlet Emergency Hospital (RSDC) in handling COVID-19 are in accordance with the rules of International Environmental Law along with Indonesian Environmental Law and whether the management of COVID-19 medical waste at the Wisma Atlet Emergency Hospital is in accordance with the rules of Indonesian Environmental Law. The type of research used is normative juridical, data processing is done qualitatively, and deductive conclusions are drawn. Based on the analysis conducted, the rules for managing COVID-19 medical waste at Wisma Atlet Emergency Hospital are in accordance with International Environmental Law made by WHO and UNEP and Indonesian Environmental Law made by the Ministry of Environment and the Ministry of Health, including the SOP of Wisma Atlet Emergency Hospital regarding medical waste management. The practice of medical waste management at Wisma Atlet RSDC is also in accordance with Indonesian Environmental Law.